2002
DOI: 10.1098/rspb.2002.2084
|View full text |Cite
|
Sign up to set email alerts
|

Biting cleaner fish use altruism to deceive image–scoring client reef fish

Abstract: Humans are more likely to help those who they have observed helping others previously. Individuals may thus benefit from being altruistic without direct reciprocity of recipients but due to gains in 'image' and associated indirect reciprocity. I suggest, however, that image-scoring individuals may be exploitable by cheaters if pay-offs vary between interactions. I illustrate this point with data on cleaner-client reef fish interactions. I show the following: (i) there is strong variation between cleaners with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(113 citation statements)
references
References 36 publications
2
110
0
Order By: Relevance
“…Moreover, observation by bystanders is an important factor of reputation. Several studies have demonstrated that observation by bystanders strongly influences some kinds of animals' behaviour (Oliveira et al 1998;Doutrelant et al 2001;Bshary 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, observation by bystanders is an important factor of reputation. Several studies have demonstrated that observation by bystanders strongly influences some kinds of animals' behaviour (Oliveira et al 1998;Doutrelant et al 2001;Bshary 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, signal reliability may not necessarily be based on genetic quality. Client fish, for instance, base their decision about whether to interact with a particular cleaner on the service quality they observed in a previous interaction of the cleaner with another client (Bshary, 2002;Bshary and Grutter, 2006). Apparently, the current behaviour of the cleaner predicts to a certain extent how cooperative the following interaction will be, therefore eavesdropping on the interactions of others appears to contain reliable information for clients (Covas et al, 2007).…”
Section: Group Augmentation: Can It Results From By-product Mutualism?mentioning
confidence: 99%
“…Apparently, the current behaviour of the cleaner predicts to a certain extent how cooperative the following interaction will be, therefore eavesdropping on the interactions of others appears to contain reliable information for clients (Covas et al, 2007). Cleaners, in turn, can make use of an eavesdropping audience to signal their (short term) quality as cleaner (Bshary and Würth, 2001;Bshary, 2002;Bshary and D'Souza, 2004;Bshary and Grutter, 2006). Signal reliability is central for prestige based explanations of cooperative investment and it remains a challenging question to determine under which conditions signal reliability can evolve (see also Covas et al, 2007) so prestige can be an explanation of helping behaviour.…”
Section: Group Augmentation: Can It Results From By-product Mutualism?mentioning
confidence: 99%
“…We expect judgement bias to evolve in any organism that exhibits image scoring, whether that be cleaner fish (Bshary 2002;Bshary & Grutter 2006) or humans ( Wedekind & Milinski 2000;Wedekind & Braithwaite 2002). Repeated interactions between the same individuals are not necessary for indirect reciprocity and judgement bias to evolve.…”
Section: Discussionmentioning
confidence: 99%